Estimating Central Blood Pressure From a Single Peripheral Pressure Measurement. Issue 15 (2021) - Murphy, Liam; Chase, Geoff; Davidson, Shaun; Desaive, Thomas
Abstract: This paper presents a set of criteria used to identify the parameters describing a tube-load model of the arterial system to estimate central blood pressure (BP). The criteria are generalizable to accommodate for inter- and intra-subject variability encountered in the ICU. The proposed single measurement transfer function (SMTF) requires only a single peripheral pressure measurement, commonly available in the ICU, for central pressure estimation, removing the need for an additional measurement of pulse transit time, common to other central BP estimation models. The method was tested using data from six (6) porcine experiments where septic shock was induced and subsequent treatment was performed. Systolic pressure (SP), pulse pressure (PP) and root-mean-squared (RMSE) errors relative to invasive measurements of aortic pressure were used to assess accuracy. The SMTF method produced mean errors ≤5mmHg across all metrics with 84.4, 88.7 and 63.2% of SP, PP, and RMSE, respectively, within this bound of measured central pressure. Peripheral BP accuracy was also assessed as it is commonly used as a surrogate for central BP in clinical settings. Finally, two alternate methods utilizing the same model equations with additional inputs, one using the measured pulse transit time and the other minimizing the RMSE with measured aortic pressure, were implemented to compare the SMTF accuracy to best case outputs given the model equations.